Dynamism in Economic Policies to Achieve Economic Stability: Evidence from Pakistan - Qayyum, Aaqib; Manzoor, Sadia (Asian Journal of Economics and Empirical Research, 2018)
Economic policies always play a crucial role to achieve the country's economic stability through the mutual integration of fiscal and monetary policies. This study is one of the initiatives to analyze the dynamism of economic policies to achieve Pakistan's economic growth while controlling public taxes, government expenditures, broad money supply, inflation, and unemployment during a period of 1980-2017. The study employed the ARDL –Bounds testing approach in order to obtain the short- and long-run elasticities under the cointegrated framework. The results show that in the short-run, tax rate largely supported the country’s economic growth, while this result is disappeared in the long-run, where high tax rate substantially decreases economic growth. The result concluded that contractionary fiscal policy is undesirable in the long-run due to large tax evasion, which negatively impacts on the country's economic growth. The results further reveal that money supply has a positive and significant impact on country's economic growth both in the short and long-run, which implies that expansionary monetary policy stimulates economic growth via the channel of domestic and foreign investment in a country. The study also suggests that state should focus on fiscal measures while monetary measures can be effective in long-term.